The adhesion of Plasmodium falciparum-infected erythrocytes to chondroitin sulfate A is mediated by P. falciparum erythrocyte membrane protein 1 - Reeder, John C. (The National Academy of Sciences, 1999)
Chondroitin sulfate A (CSA) is an important receptor for the sequestration of Plasmodium falciparum in the placenta, but the parasite ligand involved in adhesion has not previously been identified. Here we report the identification of a var gene transcribed in association with binding to CSA and present evidence that the P. falciparum erythrocyte membrane protein 1 product of the gene is the parasite ligand mediating CSA binding. Description of this gene and the implication of P. falciparum erythrocyte membrane protein 1 as the parasite ligand paves the way to a more detailed understanding of the pathogenesis of placental infection and potential therapeutic strategies targeting the interaction.